Hydromagnetic Unsteady Mixed Convection and Mass Transfer Flow Past a Vertical Porous Plate Immersed in a Porous Medium With the Hall Effect - SHARMA, B. K.; CHAUDHARY, R. C. (Engineering Transactions, 2014)
The present work is concerned with unsteady mixed convection and mass transfer flow with Hall effect of an electrically conducting incompressible viscous fluid through a porous medium bounded by an infinite vertical plate subjected to suction/injection velocity in the presence of a constant magnetic field. The magnetic field is applied transversely to the direction of the flow. The resulting problem has been solved analytically and the solutions are found for velocity, temperature, concentration of the species, skin-friction, surface heat flux and mass flux. The effects of material parameters on the flow characteristics are expressed and illustrated/discussed by graphs and table.